PEMBANGUNAN DESA PEDALAMAN DI DESA LONG NYELONG KECAMATAN BUSANG KABUPATEN KUTAI TIMUR - Antonius Mering; Achmad Djumlani; Syahrani . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The issues raised in this research are how is the implementation of hinterland rural development that conducted in Long Nyelong Village Subdistrict Busang in East Kutai and what are the potentials of natural resource and human resource to support the development in Long Nyelong Village Subdistrict Busang in East Kutai Regency and also what are the barriers to implement the development of hinterland rural in Long Nyelong Village Subdistrict Busang in East Kutai Regency. In this study the writer uses descriptive research with qualitative approach and the data analysis that is used in this study will be used with qualitative method, the research will describe and analyze the data that have been obtained, and furthermore they will be elaborated in an actual explanation.